COVID-19 vaccines side effects among the general population during the pandemic: a cross-sectional study - Samana Zaidi; Hafsa Abdul Qayyum; Izzah Abdul Qayyum; Zakir Khan; Taskeen Islam; Naveed Ahmed; Kathryn L. Hopkins; Theresa Sommers; Samar Akhtar; Shahzad Ali Khan; Sumbal Javed; Aamer Ikram; et al. (Frontiers in Public Health)
Background and aimsThe general population have depicted concern about the safety and efficacy of the vaccine and its long-term effects on human health. Pakistan being on the verge of the pandemic is in more demand for vaccination and immunization. Therefore, this study aimed to evaluate the COVID-19 vaccines side effects among the general population.MethodsA cross-sectional face-to-face study was carried out among individuals who received either the first dosage or both doses of vaccination in twin cities (Islamabad and Rawalpindi) of Pakistan. Data was collected through a self-administered questionnaire. The questionnaire included three sections (socio-demographic, medical history, vaccine, and immunization) with 20 questions. The collected data was analyzed in SPSS (version 25) using descriptive statistics, the chi-square test, and the odd ratio.ResultsA total of 2,618 participants were included and of them, females (55.3%; n = 1,449) were more than males. The majority of the participants reported the use of precautionary medicines including vitamin C (1,319; 50.4%) followed by paracetamol (n = 1,249; 47.7%) and mineral supplements (n = 616; 23.5%) for COVID-19. In this study, 3.8% (n = 99) were unvaccinated and the first and second doses of the vaccine was received by 2,519 and 2,239 of the participants, respectively. Different types of side effects were highlighted in the current study. The most frequently reported side effects after the first dose of COVID-19 were fever (n = 997), pain at the injection site (n = 994), muscle pain (n = 620), and fatigue (n = 482). Additionally, pain at the injection site (n = 852), fever (n = 815), and muscle pain (n = 601) were commonly reported after the 2nd dose of COVID-19. The lowest reported side effects were swollen lymph nodes and anaphylactic shock. In the current study, people who were previously immunized with the flu and pneumonia vaccine had a lower risk of developing side effects (p < 0.05).ConclusionThis study highlights important information about side effects reported due to the COVID-19 vaccinations. Moreover, the use of precautionary medications was also highlighted. These findings could have a valuable impact on designing future comparative studies and developing policies/guidelines for pandemic preparedness.